ANALISIS SALAH SATU OBAT HERBAL DI SUMATERA UTARA TAHUN 2021 - Christivo Tambusai; Nerdy Nerdy; Firdaus Fahdi (Jurnal Penelitian Farmasi & Herbal, 2022)
The existence of competition between chemical and traditional drugs has resulted in increasingly being displaced from the market. In addition, another problem that traditional medicine has not been widely used for both self-medication and formal health services is that most of the efficacy of traditional medicine has not been scientifically tested. Therefore, it is very important to do an analysis through research. The purpose of this study was to determine the efficacy of traditional medicine PT. Amanah Berkah Kencana in improving health and body immunity. The research method used in this study is a descriptive method with a cross- sectional approach. The main informants in this study were consumers of traditional medicine PT. Amanah Berkah Kencana. This research was conducted in North Sumatra from December 2021 to February 2022. The results of the study explain that 82.5% strongly agree. The results of this percentage show a very good picture for consumers who use Haseda traditional medicine in maintaining health and increasing human immunity. The remaining 17.5% do not agree because of lack of public education and knowledge about the use and benefits of traditional medicine for health. For health observers, there should be socialization to the public about the use of traditional medicines.